Storming the beachhead: An examination of developed and emerging market multinational strategic location decisions in the u.s. - Denise R. Dunlap; Roberto S. Santos (Journal of Risk and Financial Management, 2021)
Entering a foreign market is challenging given the fierce competition posed by local incumbents. The literature suggests that when entering a foreign market, it is advantageous to locate where there are agglomeration benefits. Given the dynamic nature of regional development, foreign firms have multiple location options. While the literature has primarily focused on developed country multinationals' (DMNEs) location decisions, emerging market multinationals (EMNEs) are increasingly becoming influential in high-tech industries. Due to differences in DMNE and EMNE resource endowments, they may consider alternative options when locating abroad and, thus, we examine these nuances. Using multinomial logistic regression, we investigate domestic and foreign location patterns of firms within the U.S. biopharmaceutical industry as of 2018. We constructed a unique dataset of 19,962 U.S. locations and examined the location patterns of DMNEs and EMNEs from 61 countries and territories. Given the heterogeneity of regional development in the U.S., we developed a typology that stratifies regions into four categories (developed, growth, transitioning, and nascent). Counterintuitively, we find that foreign multinationals are more likely to be attracted to less developed regions than domestic firms and have different location patterns, not only compared to domestic firms, but also with respect to each other.
Keywords: 330; biopharmaceutical industry; DMNE; EMNE; foreign direct investment; location decisions; multinationals; regional resources; resource-based view